Strategy for Implementation of Transfer of Mayor's Partial Authority to Head District Policy at Bekasi City - Andy Frengky; Ummu Salamah; Iwan Satibi (Doctoral Program of Social Science Pasundan University, 2023)
This research is motivated by the phenomenon of public service problems in delegating the authority of the mayor to the sub-district head in Bekasi City. The formulation of the research problem is how the implementation and policy strategy of delegating some of the authority of the Mayor to the Camat in the field of public services in Bekasi City. This research focuses on analyzing the implementation of the policy of delegating some of the mayor's authority to the sub-district head in Bekasi City in the aspect of public services. This study aims to determine the implementation of the policy of delegating part of the authority of the Mayor of Bekasi to the sub-district head in the field of public services and to analyze the strategy that must be carried out by the Bekasi City Government so that the delegation of some of the authority of the Mayor of Bekasi to the sub-district head in the field of public services can be implemented effectively. This study uses the theory of implementation effectiveness proposed by Richard Matland. The researcher used descriptive analysis method with a case study approach. Data collection techniques were carried out through interviews, observations, literature studies and document studies. The strategy analysis carried out in this study uses a SWOT analysis with the final result being to produce a strategy for the implementation of the policy of delegating some of the mayor's authority to the sub-district head in Bekasi City. The results of this study are: 1). The implementation of the policy of delegating some of the mayor's authority to the sub-district head in Bekasi City is carried out according to the goals and objectives of the policy program. The driving factors for success are: policy accuracy, implementation accuracy, target accuracy and environmental accuracy. 2). The results of the SWOT analysis are in Quadrant I so that the strategy implemented is to support an aggressive growth policy (Growth oriented strategy) through: expanding the scope of licensing authority delegated to the sub-district head, optimizing information technology resources and empowering the role of community groups.